DETERMINASI KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PALI - Juliansyah, Arista; Hartati, Sukmini; Oktoarida, Anggeraini (Universitas Patria Artha, 2024)
The purpose of this study is to identify factors that affect the quality of PALI government financial reporting. The independent variables in this study are HR Capacity, Organizational Commitment, Information Technology Utilization and Government Internal Control System. While the dependent variable in this study is the Quality of Financial Statements. This study involved 29 OPDs and a sample of 87 finance/accounting employees in the OPDs of PALI Regency. The population of this study is OPD. Questionnaire distribution is a data collection method that uses primary data. SPSS (Statistical Package for Social Science) Version 29 program was used for Multiple Linear Regression analysis. The results in this study indicate that HR Capacity, Information Technology Utilization, Government Internal Control System (SPIP) have a significant effect on the Quality of Local Government Financial Statements while Organizational Commitment has no significant effect on the Quality of Local Government Financial Statements in PALI Regency.